Penguatan Wisata Heritage Melalui Pelatihan Sapta Pesona dan Hospitalitas untuk Kusir Dokar di Denpasar: Penguatan Wisata Heritage Melalui Pelatihan Sapta Pesona dan Hospitalitas untuk Kusir Dokar di Denpasar - Antara, Ida Bagus Ketut Soma (LOSARI DIGITAL, 2024)
The Training of Sapta Pesona and Hospitality for Dokar Drivers in Denpasar City aims to enhance the professionalism and service of dokar drivers in the Denpasar Heritage City Tour program. This goal is expected to provide a pleasant experience for tourists and address potential challenges during the tour. The training method involves collaboration between the Denpasar City Tourism Office and the International Tourism and Business Institute (IPB International), using face-to-face seminars as the main technique. A speaker from IPB International delivered material on Sapta Pesona and hospitality principles over a duration of 100 minutes to eight dokar drivers. The results of the activity showed an improvement in the dokar drivers' understanding of Sapta Pesona and its application in tourism services. The participants, most of whom did not have a formal educational background in tourism, demonstrated a good understanding of the elements of Sapta Pesona and were able to implement them, expected to enhance the quality of tourists' experiences in Denpasar. Keywords; Sapta Pesona, cart driver, hospitality, heritage, Denpasar